2021
DOI: 10.1155/2021/8874988
|View full text |Cite
|
Sign up to set email alerts
|

Smart Nursing Homes: Self‐Management Architecture Based on IoT and Machine Learning for Rural Areas

Abstract: The rate of world population aging is increasing. This situation directly affects all countries socially and economically, increasing their compromise and effort to improve the living conditions of this sector of society. In environments with large influxes of elderly people, such as nursing homes, the use of technology has shown promise in improving their quality of life. The use of smart devices allows people to automate everyday tasks and learn from them to predict future actions. Additionally, smartphones … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Urinary real-time nursing model based on medical Internet of Things (IoTs) mainly aims at nurses' daily management of urinary disease patients' nursing work, realizes the informatization and standardization of nursing work, and ensures the smooth progress of nurses' mobile nursing work for patients [ 1 ]. According to the patient information and medication information or blood information collected by the handheld device, the real-time nursing model can accurately check the patient's information during the infusion process, the oral medication process, the blood sample collection process, and the vital signs input process [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Urinary real-time nursing model based on medical Internet of Things (IoTs) mainly aims at nurses' daily management of urinary disease patients' nursing work, realizes the informatization and standardization of nursing work, and ensures the smooth progress of nurses' mobile nursing work for patients [ 1 ]. According to the patient information and medication information or blood information collected by the handheld device, the real-time nursing model can accurately check the patient's information during the infusion process, the oral medication process, the blood sample collection process, and the vital signs input process [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the studies are inconsistent on the relationship between group actives and wellbeing, our results showed that social interaction enhance higher cognition, which is a factor to ameliorate wellbeing. In fact, technology skills or social group networking skills gives the senior a greater chance of accessibility to government and health-related services that can reduce individual expenditures as well [ 63 ]. Despite the limitations of this study, our findings provide insights for future studies as opportunities of social and community engagement could provide those in need, with a causal pathway to stay organized and maintain the relationship between daily routine and self-management behavior [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the limitation of working hours remains a hurdle to achieving better results [ 36 , 37 ]. Studies have long been calling for the development of caring partnerships between nursing staff and families [ 38 ], embracing of advanced nursing plans [ 101 ], introducing self-management intelligent nursing home frameworks [ 102 ], meeting nursing staff’s educational needs [ 98 ], and avoiding violence among residents [ 103 , 104 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the rural institutional elder care system should be standardized, so that the innovation research of rural institutional elder care models is required for accumulation. In recent years, intelligent nursing homes [ 102 ], telemedicine [ 35 , 85 , 86 ], and other emerging topics have received more attention. Further research on new rural institutional elder care models assisted with emerging technologies will significantly help improve the life quality of rural institutional elder care residents and enhance their wellbeing.…”
Section: Discussionmentioning
confidence: 99%